Atrial fibrillation self-screening, management and guideline recommended therapy (AF SELF SMART): improving AF screening in general practice by utilising self-screening stations in GP waiting rooms. (14th October 2021) - Giskes, K; Lowres, N; Li, J; Orchard, J; McKenzie, K; Hespe, C; Freedman, B
Abstract: Background: Opportunistic screening for silent atrial fibrillation (AF) is recommended to reduce stroke, but screening rates are sub-optimal in Australian general practice (<15%), with practitioners reporting time constraints being the main barrier. Previous AF screening interventions in general practice have not been able to exceed screening rates of ∼34% eligible patients which is sub-optimal for stroke prevention. Purpose: To increase the proportion of patients screened for AF in general practice by implementing AF self-screening stations in waiting rooms. Methods: We developed and tested an AF self-screening station using a single-lead ECG and app with automated ECG analysis. We also developed customised software which fully integrates the self-screening station with GP medical software and the practice workflow (Figure 1). The system: 1) automatically identifies eligible patients (aged ≥65 years, no AF diagnosis) from the practice appointment diary, and sends an SMS regarding self-screening prior to their appointment; 2) automatically creates individualised patient QR codes, which provided to the patient by the receptionist; 3) the patient then scans QR code and self-screens at station in waiting room; 4) the ECG and result are automatically imported into patient record before the GP consultation. Results: Three general practices in New South Wales, Australia, were recruited. Each practice participated for approximately 3-months (between August 2020 and March 2021). During this period 825 patients completed AF self-screening, mean age 74.2 years and 45% male. When expressed as a proportion of the actual eligible patients attending the practice during the study period, the mean proportion screened in practices was 52% (range 38–65%). The device algorithm indicated "Possible AF" in 37/825 patients (4.5%); mean age 77.2 years 43% male. Conclusion: An AF self-screening station placed in GP waiting rooms that is integrated with the practice software and workflow may achieve higher screening rates for AF in general practice than standard practice, and therefore contribute to greater reductions in stroke. Funding Acknowledgement: Type of funding sources: Private grant(s) and/or Sponsorship. Main funding source(s): Investigator-lead grant from Bristol Myers Squibb and Pfizer